CT fluoroscopy-guided percutaneous drainage: comparison of the one step and the Seldinger techniques. Issue 3 (4th May 2017) - Kajiwara, Kenji; Yamagami, Takuji; Ishikawa, Masaki; Yoshimatsu, Rika; Baba, Yasutaka; Nakamura, Yuko; Fukumoto, Wataru; Awai, Kazuo
Abstract: Objective: To evaluate the one step technique compared with the Seldinger technique in computed tomography (CT) fluoroscopy-guided percutaneous drainage of abdominal and pelvic abscess. Material and methods: Seventy-six consecutive patients (49 men, 27 women; mean age 63.5 years, range 19–87 years) with abdominal and pelvic abscess were included in this study. Drainages were performed with the one step ( n = 46) and with the Seldinger ( n = 48) technique between September 2012 and June 2014. Results: The technical success and clinical success rates were 95.8% and 93.5%, respectively, for the one step group, and 97.8% and 95.7%, respectively, for the Seldinger group. The mean procedure time was significantly shorter with the one step than with the Seldinger method (15.0 ± 4.3 min, range 10–29 min vs. 21.0 ± 9.5 min, range 13–54 min, p < .01). The mean abscess size and depth were 73.4 ± 44.0 mm and 42.5 ± 19.3 mm, respectively, in the one step group, and 61.0 ± 22.8 mm and 35.0 ± 20.7 mm in the Seldinger group. Conclusion: The one step technique was easier and faster than the Seldinger technique. The effectiveness of both techniques was similar for the CT fluoroscopy-guided percutaneous drainage of abdominal and pelvic abscess.